2006
DOI: 10.2144/000112117
|View full text |Cite
|
Sign up to set email alerts
|

Toward Silencing the Burden of Malaria: Progress and Prospects for RNAi-based Approaches

Abstract: The discovery of RNA interference (RNAi) is one of the most significant of recent years, with potential for application beyond the laboratory to the clinic. As a tool for functional genomics, RNAi has permitted the characterization of genes in organisms that had previously remained recalcitrant to targeted gene manipulation. Efforts to understand its mode of action have revealed a central role in gene regulation and host defense. Finally, as a therapeutic tool, it has shown enormous promise in the control of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 54 publications
0
15
0
Order By: Relevance
“…RNA interference (RNAi) is a highly favoured method for determining the function of gene products in mosquitoes (Brown and Catteruccia, 2006), because injection of gene-specific dsRNA reduces expression of the gene and creates a 'temporary null mutation'. This approach was used to silence expression of a putative A. gambiae AKHR, previously identified as a homolog of the D. melanogaster AKHR that is generously expressed throughout the body of all A. gambiae life stages .…”
Section: Rna Interferencementioning
confidence: 99%
“…RNA interference (RNAi) is a highly favoured method for determining the function of gene products in mosquitoes (Brown and Catteruccia, 2006), because injection of gene-specific dsRNA reduces expression of the gene and creates a 'temporary null mutation'. This approach was used to silence expression of a putative A. gambiae AKHR, previously identified as a homolog of the D. melanogaster AKHR that is generously expressed throughout the body of all A. gambiae life stages .…”
Section: Rna Interferencementioning
confidence: 99%
“…Recent developments, including transgenic vectors (Christophides 2005;Sperança and Capurro 2007), RNA interference (RNAi; Blair et al 2006;Brown and Catteruccia 2006;de la Fuente et al 2006a), and pathogen-derived antigens for development of transmission-blocking vaccines Kedzierski et al 2006;Saul 2007), have shown to be a promising alternative for the control of ticks and tick-borne pathogens. However, a limited number of vaccines against arthropods resulting in generation of antigen-specific antibodies and injury to the arthropod during feeding have been reported (de la Fuente et al 1998(de la Fuente et al , 2007aValenzuela et al 2001;Lal et al 2001;Almeida and Billingsley 2002;Suneja et al 2003;de la Fuente and Kocan 2003;Willadsen 2004;Milleron et al 2004;Titus et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The application of RNAi strategies in Plasmodia is a highly contentious issue since there is currently no evidence for significant homologs of the RNAi machinery in this organism (Brown and Catteruccia, 2006). The use of chemical inhibition and functional genomics-based techniques therefore becomes more valuable but conclusive proof-of-principle of smallmolecule based target validation for P. falciparum is not as evident as for other organisms ( [Cowman and Crabb, 2003] and [Joachimiak et al, 2001]).…”
Section: Validation Of Drug Targetsmentioning
confidence: 99%